Government communication in time of legitimacy crisis - Guerra Salas, Sandra (2017)
The relationship between communication and politics is becoming increasingly narrow and it is impossible to separate both. In the present article a study of what through time has been called political communication is developed, and in most academic sections of the region, it is usually divided into three fields: electoral, governmental and crisis; reaching the present times with the development of political communication in networks, used by politicians and governors to reach the general public.